Inositol polyphosphates regulate and predict yeast pseudohyphal growth phenotypes. - Kaitlyn L Norman; Christian A Shively; Amberlene J De La Rocha; Nebibe Mutlu; Sukanya Basu; Paul J Cullen; Anuj Kumar (PLoS Genetics)
Pseudohyphal growth is a nutrient-regulated program in which budding yeast form multicellular filaments of elongated and connected cells. Filamentous growth is required for virulence in pathogenic fungi and provides an informative model of stress-responsive signaling. The genetics and regulatory networks modulating pseudohyphal growth have been studied extensively, but little is known regarding the changes in metabolites that enable pseudohyphal filament formation. Inositol signaling molecules are an important class of metabolite messengers encompassing highly phosphorylated and diffusible inositol polyphosphates (InsPs). We report here that the InsP biosynthesis pathway is required for wild-type pseudohyphal growth. Under nitrogen-limiting conditions that can induce filamentation, InsPs exhibit characteristic profiles, distinguishing the InsP7 pyrophosphate isoforms 1PP-InsP5 and 5PP-InsP5. Deletion and overexpression analyses of InsP kinases identify elevated levels of 5PP-InsP5 relative to 1PP-InsP5 in mutants exhibiting hyper-filamentous growth. Overexpression of KCS1, which promotes formation of inositol pyrophosphates, is sufficient to drive pseudohyphal filamentation on medium with normal nitrogen levels. We find that the kinases Snf1p (AMPK), Kss1p, and Fus3p (MAPKs), required for wild-type pseudohyphal growth, are also required for wild-type InsP levels. Deletion analyses of the corresponding kinase genes indicate elevated InsP3 levels and an absence of exaggerated 5PP-InsP5 peaks in trace profiles from snf1Δ/Δ and kss1Δ/Δ mutants exhibiting decreased pseudohyphal filamentation. Elevated 5PP-InsP5:1PP-InsP5 ratios are present in the hyperfilamentous fus3 deletion mutant. Collectively, the data identify the presence of elevated 5PP-InsP5 levels relative to other inositol pyrophosphates as an in vivo marker of hyper-filamentous growth, while providing initial evidence for the regulation of InsP signaling by pseudohyphal growth kinases.